2017
DOI: 10.1590/1678-7757-2016-0436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetable oils applied over acquired enamel pellicle on initial erosion

Abstract: Objective The prevalence of dental erosion has been recently increasing, requiring new preventive and therapeutic approaches. Vegetable oils have been studied in preventive dentistry because they come from a natural, edible, low-cost, and worldwide accessible source. This study aimed to evaluate the protective effect of different vegetable oils, applied in two concentrations, on initial enamel erosion.Material and Methods Initially, the acquired pellicle was formed in situ for 2 hours. Subsequently, the enamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…Reinforcement of the pellicle's protective properties by modifying its composition has been supposed in recent years as a promising novel approach in preventative dentistry (Siqueira et al, 2012;Vukosavljevic et al, 2014;Weber et al, 2015). Beside the application of polyphenolic agents for improving the pellicle's physiological function (Weber et al, 2015), it has been demonstrated that lipophilic components reveal the potential to modulate the process of bioadhesion on the tooth surface, and to modify the interfacial interactions between the pellicle-covered tooth and the surrounding oral environment (Wiegand et al, 2007;Hannig et al, 2012Hannig et al, , 2013Reich et al, 2013;Cukkemane et al, 2015;Valentijn-Benz et al, 2015;Ionta et al, 2017). Enrichment of lipids in the pellicle could be effective in protecting the tooth surface against demineralisation and bacterial biofilm formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforcement of the pellicle's protective properties by modifying its composition has been supposed in recent years as a promising novel approach in preventative dentistry (Siqueira et al, 2012;Vukosavljevic et al, 2014;Weber et al, 2015). Beside the application of polyphenolic agents for improving the pellicle's physiological function (Weber et al, 2015), it has been demonstrated that lipophilic components reveal the potential to modulate the process of bioadhesion on the tooth surface, and to modify the interfacial interactions between the pellicle-covered tooth and the surrounding oral environment (Wiegand et al, 2007;Hannig et al, 2012Hannig et al, , 2013Reich et al, 2013;Cukkemane et al, 2015;Valentijn-Benz et al, 2015;Ionta et al, 2017). Enrichment of lipids in the pellicle could be effective in protecting the tooth surface against demineralisation and bacterial biofilm formation .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that sphingosine, phytosphingosine or sphinganine protect hydroxyapatite discs against acid-induced demineralisation under in vitro conditions by forming a diffusion barrier on the hydroxyapatite surface (Valentijn-Benz et al, 2015). Using an in situ/ex vivo approach it could be shown recently that also palm oil has the potential to prevent enamel erosion (Ionta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“… 16 ( Table 1 ) The lipids collaborate with other components to contribute to the permeability of the acquired salivary pellicle. 17 , 18 Permeability is the basis of the pellicle's resistance to the acid in the oral cavity. 17 , 18 Thus, acquired salivary pellicle retards the diffusion of lactic acid to the enamel pellicle.…”
Section: Composition and Structure Of Mature Salivary Pelliclementioning
confidence: 99%
“… 17 , 18 Permeability is the basis of the pellicle's resistance to the acid in the oral cavity. 17 , 18 Thus, acquired salivary pellicle retards the diffusion of lactic acid to the enamel pellicle. 17 , 18 Furthermore, lipids influence the ultrastructure of a pellicle and modify the outer layer of the pellicle via lipid micelles.…”
Section: Composition and Structure Of Mature Salivary Pelliclementioning
confidence: 99%
“…To improve this protection, different approaches have been proposed to modify the AEP. Natural oils can increase the fatty acid content of the AEP, improving its protective properties [Reich et al, 2013;Ionta et al, 2017]. Polyphenols can bind to AEP proteins, attract more proteins and thereby increase the thickness and reduce the permeability of the AEP [Joiner et al, 2003[Joiner et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%